2014
DOI: 10.1039/c4cc04159c
|View full text |Cite
|
Sign up to set email alerts
|

19F NMR indicator displacement assay using a synthetic receptor with appended paramagnetic relaxation agent

Abstract: An admixture of zinc(II)-bis(dipicolylamine) receptor with covalently attached paramagnetic relaxation agent and fluorine-labeled phosphate indicator enables 19F NMR detection of phosphorylated analytes with amplified switched-on signal intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Smith and co-workers have recently developed an Zn(II)-bis(dipicolylamine) IDA receptor using 19 F NMR for PPi detection. 27 In this example, the bis-Zn(II)-bis-(dipicolylamine) receptor was covalently attached to paramagnetic relaxation agents, a nitroxide motif (28) and Gd(III)-DOTA (29). The addition of the 19 F-labeled phosphate indicator resulted in the expected broadening and reduction in height of the corresponding 19 F NMR signal.…”
Section: Ida-based Sensors For Phosphate-based Speciesmentioning
confidence: 99%
“…Smith and co-workers have recently developed an Zn(II)-bis(dipicolylamine) IDA receptor using 19 F NMR for PPi detection. 27 In this example, the bis-Zn(II)-bis-(dipicolylamine) receptor was covalently attached to paramagnetic relaxation agents, a nitroxide motif (28) and Gd(III)-DOTA (29). The addition of the 19 F-labeled phosphate indicator resulted in the expected broadening and reduction in height of the corresponding 19 F NMR signal.…”
Section: Ida-based Sensors For Phosphate-based Speciesmentioning
confidence: 99%
“…Alternatively, NMR-based chemosensors have been realized such that analyte binding is signaled by chemical shift changes for specific resonances of the receptor. 18,20 Being virtually free from background interferences, 19 F or 129 Xe nuclear spins offer maximum sensitivity to probe the ligand−receptor association. Furthermore, the high sensitivity of 19 F or 129 Xe chemical shifts to the local environment results in detectable changes in the NMR spectra upon analyte association to the receptor.…”
Section: ■ Discussionmentioning
confidence: 99%
“…An additional advantage of 19 F NMR‐based chemosensing is the possibility of conjugate detection with imaging (e.g., magnetic resonance imaging (MRI)). Such an approach has been explored by several groups and in particular by Kikuki, Smith, and Gao . In their studies, the degradation of complexes of paramagnetic metal ions with ligands containing 19 F nuclei or of fluorinated surfactant aggregates was used to obtain substrate‐dependent tuning of the relaxation time, thus enabling both NMR and MRI detection.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In this way,a nalyte detection also allows unambiguous identification.F ollowing as imilar strategy,Schillerand co-workers have recently shown that fluorinatedb oronic acids can be used to detecta nd discriminate diol-containinga nalytes. [7,11] An additional advantage of 19 FNMR-basedchemosensing is the possibility of conjugate detection with imaging (e.g.,m agnetic resonance imaging (MRI)).S uch an approach has been explored by severalg roups and in particularb yK ikuki, [12] Smith, [13] and Gao. [14] In their studies,t he degradationo fc omplexeso fp aramagnetic metal ions with ligands containing 19 F nuclei [12,13] or of fluorinated surfactant aggregates [14] was used to obtain substrate-dependent tuning of the relaxation time, thus enablingboth NMR and MRI detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation